Production and characterization of glutathione-chitosan conjugate films as systems for localized release of methotrexate (2019)
ABSTRACT: Cancer is one of the most serious public health problems that affect humanity. Diverse delivery systems of anticancer drugs have been developed to enhance the treatment effectiveness and patient compliance. Thus, drug delivery systems from polymeric films could be an interesting and promising alternative, especially for skin chemotherapeutics. In this work, polymeric films based on glutathione-chitosan conjugates with degrees of thiolation of 4.4%, 5.1% and 7.0% were synthetized by casting-evaporation method and subsequent loading with methotrexate. The surface properties of these films were evaluated by contact angle and spreading rate measurements. The sessile drop methods along with the thermodynamic parameter of work of adhesion were determined using the Young–Dupré semi-empirical model. The in vitro methotrexate release was assessed at a pH of 4.5 and 7.4 simulating physiological conditions. Data from the resulting profiles were fitted to the order one, Higuchi, Peppas–Sahlin and Korsmeyer–Peppas kinetic models. The results suggest a strong relationship between the thiolation degree and hydrophilic surface properties such as contact angle and water spreading rate, whereas the work of adhesion was not significantly affected. Further, these polymer films could control the methotrexate release through diverse mechanisms such as diffusion and relaxation depending on the thiolation degree and the aqueous medium employed. In fact, as thiolation degree increased, the release mechanism shifted from a primary diffusional type towards a predominant relaxation-driven mechanism. These polymer films could be used as modified systems for anticancer local delivery.